ANALISA PERBAIKAN CSR MELALUI KEPUASAN MASYARAKAT PENERIMA BANTUAN - Lissa Rosdiana Noer (2477 - 6165, 2018)
Corporate Social Responsibility is part of the strategy and management policy for a company, as compensation for implementing business activities that indirectly affect to the community activities and the environment around it. There are several CSR patternsthat can be applied: the involvement of companies, foundations or corporate social organizations, partnering with other parties, and supporting or joining a consortium. CSR is signed to be successful if the recipient community is satisfied. Satisfaction levelwas analyzed using the Service Quality Method, assuming the company has implemented 3P (Profit, People, Planet) and knews public expectations. The results of data processing using GAP analysis showed that CSR needed to be improved in Sumberrejo Village, Banyuglugur and Binor Villages, among others: improvements in the four companies' efforts in providing improvements, sustainable wished by companies in providing CSR sustainability, increasing community capacity to solve problems using training ever given, and improved conditions for CSR assistance. Improvements were needed to improve the quality of next CSR. Keywords: Corporate Social Responsibility, Service Quality, Profit, People, Planet.